(untitled) (International Journal of Engineering and Computer Science, 2015)
Aim of Software testing is to evaluate an attribute or capability of system and determine that whether it meets required prospects. The most rationally challenging part of testing is to design of test cases. Now a days, UML has been extensively used for object oriented modeling and design. This is due to the fact that UML metamodel extends support to describe structural and behavioural aspects of an architecture. However, it is still difficult to understand this behaviour, because the size of automatically generated model diagrams tends to be huge. To overcome this problem of software visualization model based slicing technique has been developed. Model based slicing is a breakdown technique to extract and identify relevant model parts or related elements across diverse model views. We have proposed a novel procedure to extract the sub- model from a big model diagrams on the basis of slicing criteria. The proposed methodology use the concept of model based slicing to slice the sequence diagram to extract the desired chunk. In the presented approach UML, conversion of UML into XML, Java DOM API for parsing and slicing has been used. Then by using the Editor Extracted Sequence Diagram has been generated.